Nasi Kaleng Sebagai Alternatif Pangan Darurat - Elvira Syamsir; Sherly Valentina; Maggy Thenawidjaja Suhartono (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2014)
Canned rice products were meeting the developed as Emergency Food Products (EFP) because of its convenience and stability as well as met eating habits of Indonesian people. The objective of this research was to produce canned-rice products as EFP that contribute the needs of daily energy intake (200 kcal), determine the effect of heat intensity during the thermal process (Fo) and rice variety to thermal characteristics and product quality. The rice formula consists of rice (36.87%), coconut milk (6.16%), block chicken broth (1.47%), salt (0.18%), and water (55.31%). The chicken formula consisted of cooked chicken meat (41.07%), coconut milk (32.86%), oil (8.21%), onion (3.09%), garlic (0.79%), nutmeg (0.55%), galingale (1.07%), coriander (0.03%), sugar (10.95% ) and salt (1.37%). Three types of rices with different amylose content, i.e.Cisadane (19.50%), IR 64 (23.88%) and IR 42 (28.24%) were used to make EFP. Thermal processing was carried out at different time–temperature schedules to achieve 15 and 20 minutes sterilized value (Fo). The product was packed in 307 x 113 silver enamel can and retorting at 121.1ºC (Tr) with CUT = 21 minutes. Amylose content and Fo value affected the color, texture and sensory properties of the products. EFP made of IR 64 and Fo value of 15 minutes was selected. The total energy value was 639.42 kcal per can (product’s weight was 200 g), which was contributed from fat (49.6%), protein (11.3%), and carbohydrate (39.1%).